Gait characteristics during crossing over obstacle in patients with glaucoma using insole foot pressure. Issue 32 (13th August 2021) - Lee, Han-Suk; Lee, Koon-Ja; Kim, Jeong-Lae; Leem, Hyun-Sung; Shin, Hyun-Jin; Kwon, Hyeok Gyu
Abstract: Background: Glaucoma, is the most common cause of irreversible visual deficits, presents as an injury to the optic nerve and it is mainly associated with elevated intraocular pressure. The main symptom of glaucoma is a reduction of the visual field, which is usually a source of complaint at the advanced stage of disease. Because of visual deficit, gait dysfunctions, including low gait speed and increased bumping into objects, postural sway, and falling are occurred. Many studies have used stopwatch or motion-sensing devices to report on gait function following glaucoma. However, there are few reports on gait dysfunction assessed by examining foot pressure. This study investigated gait ability following glaucoma according to different gait conditions by assessing foot pressure. Methods: Thirty older adults (15 in the sex- and age-matched normal group and 15 in the glaucoma group) were recruited for this study. All participants were walked under 2 different gait conditions in an F-scan system and the subject' assessments were randomly assigned to rule out the order effect. Conditions included: gait over an obstacle in a straight 6 m path, gait in a straight path without an obstacle in the 6 m path. Gait variables included cadence, gait cycle, stance time, center of force (COF) deviation, and COF excursion. About 10 minutes were taken for gait evaluation. Results: When walking without an obstacle on a 6 m path, there were significant differences between the 2 groups in gait speed, cadence, gait cycle, and stance time ( P  < .05). There were significant differences when walking with an obstacle on a 6 m path ( P  < .05). Two-way analysis of variance showed significant effects associated with "glaucoma" not gait condition on all outcomes except for COF deviation and excursion. Also, there was no the interaction effect between "glaucoma" and "gait condition." Conclusion: We demonstrated that glaucoma patients selected the gait strategy such as lower gait function in both gait conditions particularly, slower gait speed and cadence and longer gait cycle and stance time, as determined by examining foot pressure. We believe that our results could help to improve the quality of life of patients with glaucoma.